DEVELOPING WEB-BASED CALLED “BLUSHY” SOCIAL NETWORK FOR NTF INFLUENCERS - Cindy Laura; Rosalina Rosalina (President University, 2022)
Blushy is a social network (Wagino, 2020) forNTF Management influencers. NTF Management is aninfluencer marketing who acts as a bridge betweenbusinesses and influencers. This final project will focus onestablishing a web-based application called “Blushy” as asocial network for NTF Management influencers.